Pattern of skin fungi in palmar arsenical keratosis (Bangladesh Journal of Pharmacology, 2018)
The aim of this study was to examine the pattern of fungi in palmar arsenical keratosis. The skin swab was taken from the five different sites (palm, dorsum, axilla, front and back of the chest) of arsenicosis patients (n=37), arsenic exposed volunteers (n=20) and healthy volunteers (n=20) of an arsenic endemic area. Fungi were cultured in the Sabouraud dextrose agar media. The skin of the healthy volunteers contained only four species of fungi: Aspergillus, Dermatophytes, Mucor and Fusarium. The incidence of each fungus was low (0-4 out of 20 cases). The chronic exposure to arsenic did not alter the pattern of fungi. However, the patient of arsenicosis showed increased inci-dence of Aspergillus and Dermatophytes species and decreased incidence of Mucor species. The supplementation of iron and folic acid to the patient for 12 weeks reduced the incidence of Aspergillus (only in axilla), Dermatophytes (only in palm) and increased the incidence of Mucor (all the sites except palm). In conclusion, skin fungi are altered in arsenicosis irrespective of intake of high concentration of arsenic.